Effect of water temperature on embryonic development of Protunus trituberculatus in an off-season breeding mode - He, Jie; Wan, Litao; Yu, Huaihua; Peng, Yingying; Zhang, Dongxu; Xu, Wenjun (Frontiers in Marine Science, 2022)
The rate of embryonic development, embryo antioxidant ability, hatching rate and digestive enzyme activity of newly hatched Protunus trituberculatus larvae were compared under different water temperature conditions in an off-season breeding mode (breeding in early autumn). The results showed that the duration of each development stage of swimming crab embryos was gradually reduced with increasing water temperature. The total development time was 9.43 d at 27 °C and only 6.88 d at 33 °C. These effects were accompanied by an increase in the development rate from 0.11 d-1 to 0.15 d-1. The highest total effective temperature (207.47 °C·d) was noted at 27 °C, whereas the values for the other three temperature groups were approximately 192 °C·d. The development of embryos at 27 °C and 29 °C was very synchronous. Conversely, at 31 °C, the later stage of development exhibited asynchrony, and diapause and death were noted in some embryos. At 33 °C, approximately 50% of embryos died. The embryo hatching rate was approximately 70% at 27 °C and 29 °C, and the rate was significantly reduced at 31 °C and 33 °C. Specifically, the rate was only 13.89% at 33 °C. As the water temperature increased, the activities ofsuperoxide dismutase（SOD） and glutathione peroxidase（GSH-PX） as well as the total antioxidant capacity （T-AOC） and malondialdehyde（MDA） levels of embryos increased first and then decreased. CAT activity exhibited the opposite trend. At temperatures of 27 ℃, 29 ℃ and 31 ℃, the differences in various digestive enzymes of newly hatched larvae primarily manifested as the high activities of pepsin (PEP) and α-amylase (AMS) at 31 ℃, and other differences were not obvious. Overall, a temperature below 29 ℃ represents the appropriate temperature for embryonic development in autumn in swimming crabs. A temperature of 31 ℃ has a greater impact on the embryo hatching rate, but the quality of the surviving embryos and newly hatched larvae is still good. However, at 33 ℃, the embryo hatching rate is very low, and the quality of the surviving embryos and newly hatched larvae is poor.